Immunohistochemical study of MMP-2, TIMP-1 in hyperplastic polyps and intestinal-type gastric adenocarcinoma. - V. A. Tumanskiy; T. A. Khrystenko (Морфологія, 2017)
Background. The process of extracellular matrix degradation, provided by the matrix metalloproteinases system, plays an important role in cancerogenesis. Objective. To study the features of immunohistochemical expression of MMP-2, TIMP-1 by hyperplastic polyps’ cells and intestinal-type gastric adenocarcinoma cells. Methods. Pathohistological and immunohistochemical studies of hyperplastic polyps from 30 patients (age ranged from 52 to 73 years), intestinal-type gastric adenocarcinoma from 30 patients (age ranged from 49 to 86 years) were investigated. Results. It has been established that hyperplastic polyps’ epitheliocytes and stromal cells are characterized by the low MMP-2 and TIMP-1 expression levels, intestinal-type gastric adenocarcinoma cancer cells – by the low expression levels of these markers, while the cells of the carcinoma microenvironment are characterized by the medium expression levels of the examined markers. The cells of the microenvironment of the non-invasive carcinoma are characterized by the higher TIMP-1 expression level, compared to the cells of microenvironment of the invasive cancer. The direct correlations between the MMP-2 and TIMP-1 expression levels in the cancer cells and the cells of cancer microenvironment, and also the reverse correlation between the TIMP-1 and caspase-3 expression levels in the cancer cells were revealed. Conclusion. This data evidence the leading role of the cancer microenvironment cells in the process of extracellular matrix degradation, and also the close association between the stromolitic activity of the various cellular components of the carcinoma. Moreover, the anti-apoptotic effect of TIMP-1 in intestinal-type gastric adenocarcinoma was revealed.